Digital technologies in policy assemblages in Ireland and Norway: A visual network analysis. (March 2021) - Lunde, Ida M; Ottesen, Eli
Increasingly, school leaders and teachers are being expected to use digital technologies to collect data to analyze, plan and organize teaching and learning. Such expectations can be traced to a number of policy initiatives over the last decade. This study is concerned with how educational policy puts forward ambitions of digital school leadership and teaching practices by deploying the concept of policy assemblage. We analyzed six policy documents from Ireland and Norway to identify the actors assembled to fulfill governmental ambitions and practices with digital technologies in schools. The unpacking of actors that may partake in such assemblages was visualized and analyzed using visual network analysis. The findings indicate digital school leadership and teaching practices in Ireland and Norway have the potential to be steered by digital actors that facilitate multiple activities at once and shed light on the diverse and multifaceted relationships that make up these governing practices.